PAKTA WARSAWA : LATAR BELAKANG, SEJARAH, DAN HEGEMONI UNI SOVIET - Elpius Kalembang; Joseph Victor Kalembang (Program Studi Imu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Timor, 2022)
National security is an ability to protect the country's essential values against threats from outside and from within the country. The concept of a country's national security is influenced by the country's historical background. For realists, security is about the survival of the state. For the majority of countries that are unable to guarantee the security of their own country with their military power, the balance of powerfor maintaining security stability in international relations. Protection of domestic security conditions requires the country to ensure the integrity of its territory. After the formation of NATO in 1949, The Soviet Union initiated a defense organization together with its neighbors. That meeting giveresult in the Pact of Mutual Assistance and Unified Command (PMAUC) or better known as the Warsaw Pact and consisted of Eastern Bloc countries or East European communists. This defense pact was formed to counter the power of NATO and protect the security of the Soviet Union and its member states from outside attacks. In particular, the formation of this defense alliance was triggered by the inclusion of West Germany in NATO membership